First report of a case of occasional hermaphroditism in Polyplacophora - Scarano, María Agostina (2009)
Hermaphroditism has been defined as the production of eggs and sperm by the same individual. Among different types of hermaphroditism, one case is the simultaneous or functional hermaphroditism in which the production of eggs and sperms is concurrently. Functional hermaphrodites are found in nearly all phyla of invertebrates and are occasionally found in gonochoristic species. These occasional cases of hermaphroditism may be considered as resulting from an alteration in the mechanism of sex determination. In occasional hermaphrodites, the proportion of male and female tissues can be variable, either having approximately the same quantity of each sexual type or one type may be represented only by a reduced number of cells of the other sexual type.